Politics and organizational capacities of selected key fiscal and social institutions in Uganda - Mesharch W. Katusiimeh; Jalia Kangave (United Nations Research Institute for Social Development (UNRISD), 2015)
This paper examines the linkages between resource mobilization and social outcomes by looking at institutions that play a key role with respect to resource mobilization and social spending in Uganda. It looks at three institutions - the Uganda Revenue Authority (URA), Kampala Capital City Authority (KCCA) and the Ministry of Health (MoH) - which were selected because they are key organizations in either revenue collection or social service delivery or both, and all three were targets of reforms with varying degrees of success. The paper compares these institutions with respect to political prioritization, and to what extent they benefit from key institutional reforms. The analysis reveals how political interests in and priorities of public institutions serve to explain differences in their organizational capacity, which is determined by the competence of employees, loyalty to ruling elites, prioritization of resource allocation and political protection. It demonstrates that only politically important organizations - those perceived to be key for the political survival of the ruling elite - are well equipped with resources. The findings also stress the point that organizations that tend to perform better do so because they are politically prioritized and offered political protection.
Keywords: 330